Creation of a Code of Ethics for Influencer Marketing: The Case of the Czech Republic. Issue 2 (3rd April 2023) - Ortová, Nina; Hejlová, Denisa; Weiss, David
ABSTRACT: Influencer marketing is an increasingly important and ubiquitous component of strategic communication campaigns, yet one that remains ethically fraught, due largely to the nonexistence of, and objections to, ethics codes and/or regulation guiding its use or disclosure. This article describes a unique academic/industry hybrid study conducted in the Czech Republic combining (a) mixed-methods research in which marketing professionals, industry associations, influencers, and consumers served as participants and (b) a case study of the subsequent development and implementation of – and positive responses to – that nation's first "Fair Influencer" Code of Ethics, whose content was based directly on the research findings. To date, the Code has 150 signatories, representing all constituencies of the influencer-marketing sphere, and has been lauded by Czech and Slovak consumer and media outlets as well as influencers themselves, suggesting the applicability of similar efforts in other nations where influencer marketing thrives but still lacks – and encounters resistance to – ethical or regulatory oversight.